Psychometric Properties and Correlates of Precarious Manhood Beliefs in 62 Nations - Bosson, J.K.; Jurek, P.; Vandello, J.A.; Kosakowska-Berezecka, N.; Olech, M.; Besta, T.; Bender, M.; Hoorens, V.; Becker, M.; Sevincer, A.T.; Best, D.L.; Safdar, S.; et al. (SAGE, 2021)
Precarious manhood beliefs portray manhood, relative to womanhood, as a social status that is hard to earn, easy to lose, and proven via public action. Here, we present cross-cultural data on a brief measure of precarious manhood beliefs (the Precarious Manhood Beliefs scale [PMB]) that covaries meaningfully with other cross-culturally validated gender ideologies and with country level indices of gender equality and human development. Using data from university samples in 62 countries across 13 world regions (N=33,417), we demonstrate: (1) the psychometric isomorphism of the PMB (i.e., its comparability in meaning and statistical properties across the individual and country levels); (2) the PMB’s distinctness from, and associations with, ambivalent sexism and ambivalence toward men; and (3) associations of the PMB with nation level gender equality and human development. Findings are discussed in terms of their statistical and theoretical implications for understanding widely-held beliefs about the precariousness of the male gender role.
Research Article
Keywords: psychometric isomorphism; precarious manhood beliefs; ambivalent sexism; ambivalence toward men